Pannexin 3 ER Ca(2+) channel gating is regulated by phosphorylation at the Serine 68 residue in osteoblast differentiation - Ishikawa, Masaki (Sci Rep, 2019)
Pannexin 3 (Panx3) is a regulator of bone formation. Panx3 forms three distinct functional channels: hemichannels, gap junctions, and endoplasmic reticulum (ER) Ca(2+) channels. However, the gating mechanisms of the Panx3 channels remain unclear. Here, we show that the Panx3 ER Ca(2+) channel is modulated by phosphorylation of the serine 68 residue (Ser68) to promote osteoblast differentiation. Among the 17 candidate phosphorylation sites identified, the mutation of Ser68 to Ala (Ser68Ala) was sufficient to inhibit Panx3-mediated osteoblast differentiation via reduction of Osterix and ALP expression. Using a Ser68 phospho-specific antibody (P-Panx3) revealed Panx3 was phosphorylated in prehypertrophic, hypertrophic chondrocytes, and bone areas of the newborn growth plate. In osteogenic C2C12 cells, P-Panx3 was located on the ER membranes. Importantly, the Ser68Ala mutation only affected Panx3 ER Ca(2+) channel function. Ser68 on Panx3 was phosphorylated by ATP stimulation and PI3K/Akt signaling. Finally, real-time FRET imaging and ratio analysis revealed that the Panx3 channel conformation was sensitive to ATP. Together, the phosphorylation of Panx3 at Ser68 is an essential step controlling the gating of the Panx3 ER Ca(2+) channel to promote osteogenesis.